Comparison of Efficacy of Deep Brain Stimulation of Different Targets in Parkinson's Disease: A Network Meta-Analysis - Mao, Zhiqi; Ling, Zhipei; Pan, Longsheng; Xu, Xin; Cui, Zhiqiang; Liang, Shuli; Yu, Xinguang (Frontiers in Aging Neuroscience, 2019)
ackground: Deep brain stimulation (DBS) is considered an effective treatment option for Parkinson’s disease (PD). Several studies have demonstrated the efficacy of neurostimulation in patients with advanced PD. The subthalamic nucleus (STN), the internal globus pallidus (GPi), ventral intermediate nucleus (Vim), and pedunculopontine nucleus (PPN) are reportedly effective DBS targets for control of Parkinsonian tremors. However, there is no consensus on the ideal target for DBS in patients with Parkinson’s disease. Only a few studies have directly compared the efficacy of DBS of the Vim, STN, and GPi. Therefore, we searched PubMed, Embase, Cochrane Library, and other databases for observational studies, extracted data on unified Parkinson's disease rating scale (UPDRS) scores and performed a comprehensive network meta-analysis of different strategies of DBS and compared the efficiency of DBS at different targets. Methods: Forest plot was used to examine the overall efficiency of DBS; cumulative probability value was used to rank the strategies under examination. A node-splitting model was employed to assess consistency of reported outcomes inconsistency. A total of 16 studies which focused on UPDRS improvement were included in the network meta-analysis. Results: By comparing the overall efficiency associated with each target, we confirmed the efficacy of DBS therapy in PD. Our findings revealed similar efficacy of DBS targeted at GPi and STN; however, in the off-medication phase, Vim-targeted DBS was associated with better improvement in UPDRS scores and could be a choice as a DBS target for tremor-dominant Parkinsonism. Conclusions: Our findings will help improve clinical application of DBS.